PERAN MEDIA SOSIAL DALAM PEMBENTUKAN AKHLAK SISWA SMP ADZKIA ISLAMIC SCHOOL SERUA INDAH CIPUTAT DI ERA DIGITAL - Syarifuddin, Syarifuddin; Rahmania, Annisa (STIT AL-AMIN KREO TANGERANG, 2024)
This study aims to analyze the impact of social media on the development of the morals of ninth grade students at SMP Adzkia Islamic School. In today's digital era, social media plays an important role in everyday life, especially for teenagers. The research methodology used is descriptive qualitative with a case study approach. Data were collected through observation, interviews, and document studies, involving students, teachers, and school staff. The results of the study indicate that the use of social media has positive and negative impacts on students' morals. The positive impacts include ease of accessing information, expanding friendship networks, and supporting distance learning. However, negative impacts were also found, such as decreasing time for religious studies, the emergence of rude behavior, and negative influences in communicating with peers. This study concludes that the use of social media needs to be monitored and directed, especially for students, so that they can use it wisely and are not influenced by its negative impacts. This study recommends intensive coaching and guidance from schools and parents in the use of social media by students to prevent negative influences that can damage their morals